Water Quality Of The Tirtoagung Reservoir Based On The Phytoplankton Diversity Index And The Saprobic Index In Sleman Yogyakarta - Rahmayanti; Sudarsono (Indonesian Journal of Bioscience (IJOBI), 2023)
Embung Tirtoagung is an artificial aquatic ecosystem as a supplier of agricultural land during the dry season and as a fishery facility in Sleman Regency. This study aims to determine the water quality in Tirtoagung Embung based on the diversity index and saprobic index. This research is an exploratory descriptive research by way of observation. The research was conducted in February – April 2021 during the rainy season. The sampling locations were at 5 stations selected by random sampling. The results of the study showed that the water quality in Tirtoagung Embung is included in the lightly polluted category. It is known from the calculation of the diversity index that is 2,391 so that the situation is in the moderate category and the Tirtoagung reservoir is in a lightly polluted condition. Then seen from the calculation of the saprobic index, which is 0.71 - 1.00 so that the condition of the waters of the Tirtoagung reservoir is in the - mesosaprobic phase with light pollution levels and few organic and inorganic compounds. In addition, the water quality of the Tirtoagung reservoir based on physical and chemical parameters is still feasible for the survival of phytoplankton.